The Absence and Discrimination of Women in the Education of History and Social Sciences Teachers - Marolla-Gajardo, Jesús (Revista Electrónica Educare, 2019)
The problem of violence and discrimination based on gender is an aspect we must take in charge as a society. In this line, the objectives of this research have been framed in the reflection on problems and obstacles that arise in teacher training, as well as on possibilities and advantages of including and working with women and their history. The research is a case study that had five participants. The participants were teachers of social science teaching who work in different establishments in Santiago, Chile. The instruments to collect information consisted of semi structured interviews, and the techniques to analyze it took into account the critical theory, poststructuralism, gender theories, and queer theory. Regarding the main findings, it is possible to point out that, for the teaching staff of didactics, there are multiple possibilities to include women and their history in teacher training, as well as in teaching practices. However, for this, spaces that favor the inclusion of women’s problems should be promoted. The participating teachers recommended, as conclusions, that women and other groups that have been invisibilized, marginalized, and have suffered violence in different contexts should reflect on their own pedagogical practices to generate spaces and transformations in face of inequalities, prejudices, stereotypes, and the oppressive roles that women have been given for reasons of gender.